Anti‐TNF‐α Activity of Brazilian Medicinal Plants and Compounds from Ouratea semiserrata. (22nd June 2015) - Campana, Priscilla R. V.; Mansur, Daniel S.; Gusman, Grasielle S.; Ferreira, Daneel; Teixeira, Mauro M.; Braga, Fernão C.
<x xml:space="preserve">Abstract</x> Several plant species are used in Brazil to treat inflammatory diseases and associated conditions. TNF‐α plays a pivotal role on inflammation, and several plant extracts have been assayed against this target, both in vitro and in vivo. The effect of 11 Brazilian medicinal plants on TNF‐α release by LPS‐activated THP‐1 cells was evaluated. The plant materials were percolated with different solvents to afford 15 crude extracts, whose effect on TNF‐α release was determined by ELISA. Among the evaluated extracts, only Jacaranda caroba (Bignoniaceae) presented strong toxicity to THP‐1 cells. Considering the 14 non‐toxic extracts, TNF‐α release was significantly reduced by seven of them (inhibition > 80%), originating from six plants, namely Cuphea carthagenensis (Lythraceae), Echinodorus grandiflorus (Alismataceae), Mansoa hirsuta (Bignoniaceae), Ouratea semiserrata (Ochnaceae), Ouratea spectabilis and Remijia ferruginea (Rubiaceae). The ethanol extract from O. semiserrata leaves was fractionated over Sephadex LH‐20 and RP‐HPLC to give three compounds previously reported for the species, along with agathisflavone and epicatechin, here described for the first time in the plant. Epicatechin and lanceoloside A elicited significant inhibition of TNF‐α release, indicating that they may account for the effect produced by O. semiserrata crude extract. Copyright © 2015 John Wiley & Sons, Ltd.